Broadband GaAs pHemt LNA design for T/R module application - Le, Phong Dai; Thong, Vu Duy; Binh, Pham Le (Vietnam Journal of Science and Technology, 2016)
In this paper, a three stages monolithic low noise amplifier (LNA) for T/R module application is presented. This LNA is fully integrated on 0.15-um pHEMT GaAs technology and achieves a wide bandwidth from 6 GHz to 11 GHz. Within this band, the LNA has the minimum of 1.3 dB noise figure and over 25 dB small signal gain. The output third order interception point (OIP3) is over 30 dBm and the 1 dB compression point (P1 dB) is 16 dBm at the output.